Some Characteristics of Hail Processes in Kakheti (Georgia) According to Radar Observations into 2016-2019 - G. Amiranashvili, Avtandil; A. Chikhladze, Victor; S. Kveselava, Nugzar; R. Kvilitaia, Nodar; P. Sauri, Ioseb; T. Shavlakadze, Shota (Journals of Georgian Geophysical Society, 2020)
The paper presents the results of a statistical analysis of such parameters of hail processes for separate municipalities of Kakheti in the period from 2016 to 2019, as: the maximum height of hail clouds, the maximum diameter of hailstone in clouds, the number of hail clouds of various categories, repetition of hail clouds of various categories, the mean hail hazard relative ratio G. In particular, it was found that during the study period , the greatest hail hazard was observed in the Gurjaani municipality (G = 1.74), and the smallest in the Dedoplistskaro municipality (G = 0.39).